A possible phytosaurian (Archosauria, pseudosuchia) coprolite from the late triassic fleming fjord group of jameson land, central east Greenland - Milàn, Jesper; Mateus, Octávio; Mau, Malte; Rudra, Arka; Sanei, Hamed; Clemmensen, Lars B. (Bulletin of the Geological Society of Denmark, 2021)
Funding Information: This project is part of a combined sedimentological, palaeontological and magnetostratigraphical investigation of the Late Triassic vertebrate-bearing continental deposits in central East Greenland supported by the Independent Research Fund Denmark. We thank Dennis V. Kent for productive discussions on Late Triassic stratigraphy. We are grateful to Karen Dybkjær, GEUS, for help with palynological examination of the coprolite. We thank Bo Markussen, Department of Mathematical Sciences at the University of Copenhagen, for guidance about statistical analyses. We gratefully acknowledge support from Dronning Margrethes og Prins Henriks Fond, Arbejdsmarkedets Feriefond, Oticon Fonden, Knud Højgaards Fond, Louis Petersens Legat, Det Obelske Familiefond, Ernst og Vibeke Husmans Fond, the Carlsberg Foundation and Geocenter Møns Klint. GEUS provided valuable logistical support. We thank Adrian Hunt and an anonymous referee for constructive reviews. A large, well-preserved vertebrate coprolite was found in a lacustrine sediment in the Malmros Klint Formation of the Late Triassic Fleming Fjord Group in the Jameson Land Basin, central East Greenland. The size and internal and external morphology of the coprolite is consistent with that of crocodilian coprolites and one end of the coprolite exhibits evidence of post-egestion trampling. As the associated vertebrate fauna of the Fleming Fjord Group contains abundant remains of pseudosuchian phytosaurs, the coprolite is interpreted as being from a large phytosaur. publishersversion published